2017
DOI: 10.3390/molecules22020304
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Study of Tapirira guianensis Leaves Guided by Vasodilatory and Antioxidant Activities

Abstract: The aim of this research was to perform a phytochemical study of the methanol leaves extract of T. guianensis (MET) guided by vasodilatory and antioxidant activities. The chemical profile of MET and the ethyl acetate fraction (EA fraction) was determined by HPLC-UV-MS and EA fraction guided fractionation by reverse-phase chromatography. The vasorelaxant effects of MET, fractions, sub-fractions and constituents were assessed on rat aorta pre-contracted with phenylephrine. Antioxidant activity was evaluated by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…In the present study, the MVB was pre-contracted with phenylephrine and wortmannin, a PI3K inhibitor. Wortmannin strongly reduced lythrine-induced vasodilatation, suggesting that PI3K-dependent activation of eNOS is an important underlying mechanism in the vasodilatory effect of lythrine, similar to that reported for Tapirira guianensis (Rodrigues et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, the MVB was pre-contracted with phenylephrine and wortmannin, a PI3K inhibitor. Wortmannin strongly reduced lythrine-induced vasodilatation, suggesting that PI3K-dependent activation of eNOS is an important underlying mechanism in the vasodilatory effect of lythrine, similar to that reported for Tapirira guianensis (Rodrigues et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…The main compounds from T. guianesis were glycosylated flavo- S6). From plants collected in distinct biomes, these compounds have been described already by Correia et al, 27 and Rodrigues et al, 28 showing that these compounds could be used as chemical markers of this species.…”
Section: Characterisation Of Secondary Metabolites By Hlpc-dad-ms/msmentioning
confidence: 74%
“…In the past decade, epidemiological studies have shown that cardiovascular diseases are the main cause of death and disability worldwide [1,2]. In Africa, cardiovascular diseases (CVD) have reached nearly epidemic proportions.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiological mechanism behind this disorder is multifactorial and include oxidative stress, inflammation, reninangiotensin system and autoimmune vascular dysfunction [5][6][7]. Hypertension is characterized by a chronic elevation of arterial blood pressure (superior or equal to 140/90 mmHg), in which abnormally increased vascular tone plays a major role in the maintenance of high blood pressure [2,8].…”
Section: Introductionmentioning
confidence: 99%